Low-Protein Diets in Diabetic Chronic Kidney Disease (CKD) Patients: Are They Feasible and Worth the Effort? - Piccoli, Giorgina B. (Nutrients, 2016)
Low-protein diets (LPDs) are often considered as contraindicated in diabetic patients, and are seldom studied. The aim of this observational study was to provide new data on this issue. It involved 149 diabetic and 300 non-diabetic patients who followed a LPD, with a personalized approach aimed at moderate protein restriction (0.6 g/day). Survival analysis was performed according to Kaplan–Meier, and multivariate analysis with Cox model. Diabetic versus non-diabetic patients were of similar age (median 70 years) and creatinine levels at the start of the diet (2.78 mg/dL vs. 2.80 mg/dL). There was higher prevalence of nephrotic proteinuria in diabetic patients (27.52% vs. 13.67%, p = 0.002) as well as comorbidity (median Charlson index 8 vs. 6 p = 0.002). Patient survival was lower in diabetic patients, but differences levelled off considering only cases with Charlson index > 7, the only relevant covariate in Cox analysis. Dialysis-free survival was superimposable in the setting of good compliance (Mitch formula: 0.47 g/kg/day in both groups): about 50% of the cases remained dialysis-free 2 years after the first finding of e-GFR (estimated glomerular filtration rate) < 15 mL/min, and 1 year after reaching e-GFR < 10 mL/min. In patients with type 2 diabetes, higher proteinuria was associated with mortality and initiation of dialysis. In conclusion, moderately restricted LPDs allow similar results in diabetic and non non-diabetic patients with similar comorbidity.